A Study of drug utilization and clinical outcomes in indoor patients of hypertensive disorders of pregnancy - Gaidhankar, Smita L.; Ramanand, Jaiprakash B.; Kadam, Parashram G.; Zende, Ajitkumar M.; Bhosale, Rama R.; Puram, Nitin N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hypertensive disorders of pregnancy are an important determinant of drug use during pregnancy. The aim of study was to assess the clinical outcome and evaluate drug utilization according to WHO core drug prescribing indicators in hypertensive disorders of pregnancy. Methods: This prospective, observational study in a tertiary care hospital was conducted in 150 pregnant women with hypertensive disorders of pregnancy from January 2014 and December 2014 who fulfilled the inclusion criteria. Antepartum and intrapartum care and the maternal and perinatal outcome were noted. The data was analyzed to evaluate clinical outcome and drug utilization according to WHO core drug use indicators. Results: Gestational hypertension was most common among hypertensive disorders of pregnancy seen in 62/150 (41.3%) women. The most common symptom was headache (48%) while sign noted was edema (69%). A total of 66% women had preterm delivery and 42% babies weighed less than 2.5 kg. Average number of drugs per encounter was 9.7. Percentage of drugs prescribed by generic name and from essential drug list was 64% and 79% respectively. The most commonly used drugs were vitamins and minerals prescribed in 100% patients followed by antihypertensive drugs (92%). The most common antihypertensive used were calcium channel blockers and anticonvulsant was magnesium sulphate. Conclusions: There was increased maternal and perinatal morbidity and operative intervention among pregnant women with hypertensive disorders of pregnancy. Most of the drugs were used appropriately and were in accordance with standard guidelines. The important problems identified were inappropriate use of antimicrobials, use of sublingual nifedipine and use of brand names in 1/4th of prescriptions.